Ativismo ministerial na implementação de políticas públicas - Melo, Gilmar dos Santos (2013)
The research aims to analyze the reasons and the unique role of prosecutors in the promotion of public policies. The opening lines deal with the evolution and expansion of the general theory of the fundamental rights in the international and national levels and that have led to the creation of a welfare state concerned with carrying out positive actions which aim at the community well-being. Thus, it is clear that, after the uneven development of the Brazilian democracy, the Constitution of 1988 not only has erected to a state socially responsible, but also built a system of guarantees which highlights the significant expansion of the Powers of the Public Ministry and has now taken an outstanding position in regard to collective rights, allowing, at the same time, its members to perform the syndication of state actions, particularly public policies, correcting the course of these administrative processes in the presence of poor management and inactivity of the public administrator when acting in defense of fundamental rights. This ministerial activism, even facing the obstacles and boundaries submitted to its pursuit, has shown an increase in actions that culminated, in the last ten years, in a significant number of judicial and extrajudicial measures that indicated the correction of public policies and actions in areas of health, education, housing and the environment. In this process of monitoring and doing, the important role of the other social characters is highlighted, especially the one of the citizen who is responsible for most of the complaints that start the initiatives of the Public Ministry and that can be deployed through a significant list of judicial and extrajudicial instruments, especially the important procedure that allows the hearing and participation of the involved in the implementation of public policies, enabling a collective even a consensual solution of the matter generated among the Public Administration. Given these initiatives, the ministerial activism has established itself as a movement of its own characteristics, aimed to guarantee the fundamental rights, especially when these are not targeted by state actions that should contribute to the achievement of the democratic state of law idealized by the Federal Constitution without any distortion of direction. Nevertheless, this activism still seeks for its full accomplishment in the practical world